Analysis of serum metabolomics in patients with different types of chronic heart failure - Jie Bingzhang; Li Qiang; Han Ling; Chen Liwei; Yang Ming (Open Medicine, 2025)
Heart failure remains a major public health issue, and there are still no reliable biomarkers for left ventricular ejection fraction (LVEF).